2019
DOI: 10.1111/add.14721
|View full text |Cite
|
Sign up to set email alerts
|

Cytisine for nicotine addiction treatment: a review of pharmacology, therapeutics and an update of clinical trial evidence for smoking cessation

Abstract: AimsTo review cytisine's history of use, pre‐clinical evidence, clinical pharmacokinetics, efficacy, adverse reactions (ARs) and safety for smoking cessation.MethodsA synoptic review of the use of cytisine as a smoking cessation medication, mechanism of action, pharmacokinetics and safety. Relevant literature on data included in these sections were identified through a search of 11 databases with additional literature obtained from reports and monographs. Three databases (PubMed, EMBASE and www.elibrary.ru) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 71 publications
2
104
0
7
Order By: Relevance
“… 84 , 85 , 86 , 87 , 88 , 89 American Indians are known to have consumed the seeds of L. anagyroides (also known as Cytisus laburnum ) for their purgative and emetic effects during rituals; traditional European medicine used alcoholic extracts of Cytisus plants for constipation, migraine and insomnia; the leaves of L. anagyroides were used as tobacco substitute during World War II. 84 , 85 , 86 , 87 , 88 , 89 In several phytochemical studies examining the biological active secondary metabolite of L. anagyroides , 90 , 91 the aqueous extract of the seeds was found to contain cytisine ( Fig. 11 ), a quinolizidone alkaloid fused to a bispidine ring with absolute configuration later assigned as 1 R ,5 S through stereoselective total synthesis.…”
Section: Plant-derivedmentioning
confidence: 99%
“… 84 , 85 , 86 , 87 , 88 , 89 American Indians are known to have consumed the seeds of L. anagyroides (also known as Cytisus laburnum ) for their purgative and emetic effects during rituals; traditional European medicine used alcoholic extracts of Cytisus plants for constipation, migraine and insomnia; the leaves of L. anagyroides were used as tobacco substitute during World War II. 84 , 85 , 86 , 87 , 88 , 89 In several phytochemical studies examining the biological active secondary metabolite of L. anagyroides , 90 , 91 the aqueous extract of the seeds was found to contain cytisine ( Fig. 11 ), a quinolizidone alkaloid fused to a bispidine ring with absolute configuration later assigned as 1 R ,5 S through stereoselective total synthesis.…”
Section: Plant-derivedmentioning
confidence: 99%
“…We hypothesized that partial glucoheptoamidation may reduce amine group toxicity, retaining cationic character of a carrier. Thus, we have chosen the compromised G3 16gh and G3 11gh and attached additionally cytisine because of its low toxicity and common usage in medicine as antismoking drug [21,35]. Our preliminary studies indicated that cytisine was nontoxic not only against normal human fibroblasts (BJ) but also against human squamous cell carcinoma (SCC-15) and U-118 human glioma cells up to 500 µM after 24 h incubation (data not shown).…”
Section: Toxicity Of Conjugatesmentioning
confidence: 99%
“…However, the peripheral effects of cytisine (e.g., on the cardiovascular system) are weaker than those of nicotine. Its effectiveness, demonstrated safety, and low price make cytisine a natural alternative to other medicines for smoking cessation [1,2]. This alkaloid is also able to cross the blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids are nitrogen-containing organic compounds found in many plants, rarely animals, microorganisms, and fungi. Cytisine (1, [(1R,5S)-1,2,3,4,5,6-hexahydro-1,5-methano-8H-pyrido(1,2a)(1,5) diazocin-8-one]) and N-methylcytisine ([(−)-1,2,3,4,5,6-hexahydro-3-methyl-1,5-methano-8H-pyrido(1,2-a)(1,5)diazocin-8-one]) are quinolizidine alkaloids exhibiting various biological activity [ 1 ]. Cytisine is an α4β2 nicotinic acetylcholine receptor partial agonist, occurring in a various plants.…”
Section: Introductionmentioning
confidence: 99%